Neurite outgrowth involves adenomatous polyposis coli protein and β-catenin - Votin, Violet (2005)
Neuronal morphogenesis involves the initial formation of neurites and then differentiation of neurites into axons and dendrites. The mechanisms underlying neurite formation are poorly understood. A candidate protein for controlling neurite extension is the adenomatous polyposis coli (APC) protein, which regulates membrane extensions, microtubules and β-catenin-mediated transcription downstream of Wnt signaling. APC is enriched at the tip of several neurites of unpolarized hippocampal neurons and the tip of only the long axon in polarized hippocampal neurons. Significantly, APC localized to the tip of only one neurite, marked by dephospho-tau as the future axon, before that neurite had grown considerably longer than other neurites. To determine whether neurite outgrowth was affected by β-catenin accumulation and signaling, a stabilized β-catenin mutant was expressed in PC12 cells, and neurite formation was measured. Stabilized β-catenin mutants accumulated in APC clusters and inhibited neurite formation and growth. Importantly, these effects were also observed was independently of the gene transcriptional activity of β-catenin. These results indicate that APC is involved in both early neurite outgrowth and increased growth of the future axon, and that β-catenin has a structural role in inhibiting APC function in neurite growth.